Two Coordination Polymers@Graphene Hybrid Electrodes for High‐Performance Supercapacitors with Enhanced Rate Capability and Specific Capacitance. Issue 6 (8th February 2022) - Sun, Xuwen; Qu, Yan; Wang, Guangming; Chen, Tingting; Wang, Guangning
Abstract: Hybrids of polyoxometalate(POM)/transition‐metal complexes/graphene‐based electrode materials not only integrate the advantages of the individual components completely but also ameliorate the shortcomings to some extent, providing an efficient approach to fabricate high‐performance supercapacitors. In this work, we synthesized two novel isostructural compounds (Co(itmb)4 [H2 VW12 O40 ] ⋅ 4H2 O (1 ) and Zn(itmb)4 [H2 VW12 O40 ] ⋅ 3H2 O (2 )) based on the Keggin ions via a hydrothermal method (itmb=1‐(imidazo‐1‐ly)‐4‐(1, 2, 4‐triazol‐1‐ylmethyl)benzene). The specific capacitance of 1 @50 %graphene (405.3 F g −1 ) and 2 @50 %graphene (339.2 F g −1 ) were 1.33 and 1.19 times of 1 and 2, respectively. In addition, the 1 @50 %graphene (93.5 %) and 2 @50 %graphene (96 %) possess higher rate performance than 1 (90 %) and 2 (91 %), suggesting a significant enhancement of the electrical performance. Abstract : Graphene hybrids with two isostructural POMCP‐based electrode materials are reported to boost specific capacitance and achieve an ultrahigh rate capability. The two novel POMCPs/graphene hybrids successfully combined the excellent electrochemical properties of POMCPs with the high conductivity of graphene. It provides a promising direction for the development of a new generation of high‐performance supercapacitor electrode materials.